Effect of exercise on the nasal transmucosal potential difference in patients with cystic fibrosis and normal subjects. Issue 12 (December 1994) - Alsuwaidan, S; Li Wan Po, A; Morrison, G; Redmond, A; Dodge, J A; McElnay, J; Stewart, E; Stanford, C F
Abstract : BACKGROUND–Normal subjects have a negative nasal transmucosal potential difference (TPD) at rest which becomes more negative with exercise. Patients with cystic fibrosis have a more negative resting nasal TPD than controls. The present study was designed to determine the effects of exercise on the TPD of patients with cystic fibrosis. METHODS–Seven subjects with cystic fibrosis and seven control subjects had their usual TPD measured at rest, and during and after a 12 minute period on an exercise bicycle designed to produce a pulse rate of 80% of their maximum predicted value. RESULTS–The normal subjects developed a more negative nasal TPD during exercise which returned towards normal at the completion of the rest period. The patients with cystic fibrosis had higher resting values which became less negative during exercise. At the end of the exercise period there was no difference between the two groups. At the end of the recovery period the results for the patients with cystic fibrosis had returned to their resting values. CONCLUSIONS–Exercise reduces the abnormally high resting values for nasal TPD in patients with cystic fibrosis. Elucidation of the mechanism for this change may help to produce functional improvement for patients with this disease.